ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP CORPORATE VALUE DENGAN VARIABEL MODERASI STOCK RETURN DAN FINANCIAL PERFORMANCE - Nathalia Nathalia; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2020)
The purposive of this research is to examine impact of good corporate governance on corporate value with moderation variables stock return and financial performance. This research uses partial least square analysis method with secondary data obtained by purposive sampling method. Research data is secondary data from ICMD, financial statements and annual reports of firm that listed in LQ45 index on the Indonesia Stock Exchange in 2016-2018 and stock price data obtained from Yahoo Finance website. The results of this reasearch is indicate a positive influence between good corporate governance on corporate value. While the results of research that has been done also shows a positive influence between good corporate governance on corporate value with moderation variables are stock return and financial performance.